Possible New Strategies for the Treatment of Congenital Hyperinsulinism - Sikimic, Jelena; Hoffmeister, Theresa; Gresch, Anne; Kaiser, Julia; Barthlen, Winfried; Wolke, Carmen; Wieland, Ilse; Lendeckel, Uwe; Krippeit-Drews, Peter; Düfer, Martina; Drews, Gisela (Frontiers in Endocrinology, 2020)
OBJECTIVE: Congenital hyperinsulinism (CHI) is a rare disease characterized by persistent hypoglycemia as a result of inappropriate insulin-secretion which can lead to irreversible neurological defects in infants. Poor efficacy and strong adverse effects of the current medications impede successful treatment. The aim of the study was to investigate new approaches to silence β-cells and thus attenuate insulin-secretion. RESEARCH DESIGN AND METHODS: In the scope of our research, we tested substances more selective and more potent than the gold standard diazoxide that also interact with neuroendocrine KATP-channels. Additionally, KATP-channel-independent targets as Ca2+-activated K+-channels of intermediate conductance (KCa3.1) and L-type Ca2+-channels were investigated. Experiments were performed using human islet-cell-clusters isolated from tissue of CHI patients (histologically classified as pathological) and islet-cell-clusters obtained from C57BL/6N (WT) or SUR1 knockout (SUR1-/-) mice. [Ca2+]c was used as a parameter for the pathway regulated by electrical activity and was determined by fura-2 fluorescence. ΔΨ was determined by rhodamine123 fluorescence and single-cannel-currents were measured by the patch-clamp-technique. RESULTS: The selective KATP-channel-opener NN414 (5 µM) diminished [Ca2+]c in isolated human CHI islet-cell-clusters and WT mouse islet-cell-clusters stimulated with 10 mM glucose. In islet-cell-clusters lacking functional KATP-channels (SUR1-/-) the drug was without effect. VU0071063 (30 µM), another KATP-channel-opener considered to be selective, lowered [Ca2+]c in human CHI islet-cell-clusters. The compound was also effective in islet-cell-clusters from SUR1-/- mice, showing that [Ca2+]c is influenced by additional effects besides KATP-channels. Contrasting to NN414, the drug depolarized ΔΨ in murine islet-cell-clusters pointing to severe interference with mitochondrial metabolism. An opener of KCa3.1 channels, DCEBIO (100 µM), significantly decreased [Ca2+]c in SUR1-/- and human CHI islet-cell-clusters. To target L-type Ca2+-channels we tested two already approved drugs, dextromethorphan and simvastatin. DXM (100 µM) efficiently diminished [Ca2+]c in stimulated human CHI islet-cell-clusters as well as in stimulated SUR1-/- islet-cell-clusters. Similar effects on [Ca2+]c were observed in experiments with simvastatin (7.2 µM). CONCLUSIONS: NN414 seems to provide a good alternative to the currently used KATP-channel-opener diazoxide. Targeting KCa3.1-channels by channel openers or L-type Ca2+-channels by DXM or simvastatin might be valuable approaches for treatment of CHI caused by mutations of KATP-channels not sensitive to KATP-channel-openers.